Flow-induced adhesion of shear-activated polymers to a substrate. (17th January 2018) - Hoore, Masoud; Rack, Kathrin; Fedosov, Dmitry A; Gompper, Gerhard
Abstract: Adhesion of polymers and proteins to substrates plays a crucial role in many technological applications and biological processes. A prominent example is the von Willebrand factor (VWF) protein, which is essential in blood clotting as it mediates adhesion of blood platelets to the site of injury at high shear rates. VWF is activated by flow and is able to bind efficiently to damaged vessel walls even under extreme flow-stress conditions; however, its adhesion is reversible when the flow strength is significantly reduced or the flow is ceased. Motivated by the properties and behavior of VWF in flow, we investigate adhesion of shear-activated polymers to a planar wall in flow and whether the adhesion is reversible under flow stasis. The main ingredients of the polymer model are cohesive inter-monomer interactions, a catch bond with the adhesive surface, and the shear activation/deactivation of polymer adhesion correlated with its stretching in flow. The cohesive interactions within the polymer maintain a globular conformation under low shear stresses and allow polymer stretching if a critical shear rate is exceeded, which is directly associated with its activation for adhesion. Our results show that polymer adhesion at high shear rates is significantly stabilized by catch bonds, while at the same time they also permit polymer dissociation from a surface at low or no flow stresses. In addition, the activation/deactivation mechanism for adhesion plays a crucial role in the reversibility of its adhesion. These observations help us better understand the adhesive behavior of VWF in flow and interpret its adhesion malfunctioning in VWF-related diseases.